2022
DOI: 10.3390/plants11192488
|View full text |Cite
|
Sign up to set email alerts
|

An Update on Effectiveness and Practicability of Plant Essential Oils in the Food Industry

Abstract: Consumer awareness and demands for quality eco-friendly food products have made scientists determined to concentrate their attention on sustainable advancements in the utilization of bioactive compounds for increasing safety and food quality. Essential oils (EOs) are extracted from plants and exhibit antimicrobial (antibacterial and antifungal) activity; thus, they are used in food products to prolong the shelf-life of foods by limiting the growth or survival of microorganisms. In vitro studies have shown that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 145 publications
0
20
0
Order By: Relevance
“…have received great attention for safety, antimicrobial efficiency and biodegradability [2,10,11]. In addition to it inexpensive cost and accessibility, it therefore remains plausible to consider ethnomedicinal plants as potential source of antimicrobial for food preservation and treatment of food borne disease.…”
Section: Ofmentioning
confidence: 99%
“…have received great attention for safety, antimicrobial efficiency and biodegradability [2,10,11]. In addition to it inexpensive cost and accessibility, it therefore remains plausible to consider ethnomedicinal plants as potential source of antimicrobial for food preservation and treatment of food borne disease.…”
Section: Ofmentioning
confidence: 99%
“…There is a trend in finding natural solutions for food protection regarding healthier, organic and cleanly labeled foods [47]. In this aspect, the challenges are maintaining consumer's acceptance, low cost and good functionality [48], which may be achieved through the use of plants' products such as the EOs.…”
Section: Applicability Of Essential Oils Against Listeria Monocytogen...mentioning
confidence: 99%
“…It is suggested that the use of EOs on packages can promote antimicrobial activity against L. monocytogenes [58]. The association between sustainable food packing using renewable sources and nanoparticles with antimicrobial properties play a key role in sustainability and performance of food packing [47,59]. The use of ZnO nanoparticles associated with EO of oregano on cellulose nanofibrils films have promoted antimicrobial activity (89.6%) against L. monocytogenes, also enhancing barriers properties against oxygen and water [58].…”
Section: Applicability Of Essential Oils Against Listeria Monocytogen...mentioning
confidence: 99%
“…EO composition varies from plant to plant, due to differences in the plant parts used for the extraction of the bioactive compound, the extraction method, or the growth environment. EOs with associated antimicrobial properties include lavender, thyme, cinnamon, vanilla, oregano, basil, and rosemary [ 14 , 15 ]. Moreover, considering the particularities of the food industry, it is fundamental to highlight that several EOs harbor Generally Recognized as Safe (GRAS) status by the FDA (Food and Drug Administration, Silver Spring, MD, USA), including basil, cinnamon, clove, coriander, ginger, lavender, menthol, nutmeg, lemongrass, oregano, rose, sage, and thyme [ 14 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…EOs with associated antimicrobial properties include lavender, thyme, cinnamon, vanilla, oregano, basil, and rosemary [ 14 , 15 ]. Moreover, considering the particularities of the food industry, it is fundamental to highlight that several EOs harbor Generally Recognized as Safe (GRAS) status by the FDA (Food and Drug Administration, Silver Spring, MD, USA), including basil, cinnamon, clove, coriander, ginger, lavender, menthol, nutmeg, lemongrass, oregano, rose, sage, and thyme [ 14 , 16 ]. In recent years, Thymus vulgaris became one of the most studied species, as it contains bioactive components that have shown antagonistic effects against foodborne bacteria, such as Listeria monocytogenes [ 17 ].…”
Section: Introductionmentioning
confidence: 99%